Dietary Flavonoids, CYP1A1 Genetic Variants, and the Risk of Colorectal Cancer in a Korean population - Young Ae Cho (Nature Portfolio, 2017)
Abstract The role of dietary flavonoid intake in colorectal carcinogenesis might differ according to flavonoid subclasses and individual genetic variants related to carcinogen metabolism. Therefore, we examined whether greater dietary intake of flavonoid subclasses was associated with a lower risk of colorectal cancer and whether CYP1A1 genetic variants altered this association. A semi-quantitative food frequency questionnaire was used to assess the dietary intake of six flavonoid subclasses (flavonols, flavones, flavanones, flavan-3-ols, anthocyanidins, and isoflavones) in 923 patients with colorectal cancer and 1,846 controls; furthermore, CYP1A1 genetic variants (rs4646903 and rs1048943) were genotyped. Among the subclasses of flavonoids, higher intake of flavonols and flavan-3-ols showed a stronger association with a reduced risk of colorectal cancer after adjusting for potential confounding factors. Carriers of the CYP1A1 rs4646903 CC homozygous variant showed a reduced risk of rectal cancer compared with that in TT carriers. The inverse association between dietary flavonol intake and colorectal cancer risk was stronger among carriers of the CC homozygous variant than among T allele carriers (P for interaction = 0.02), particularly for rectal cancer (P for interaction = 0.005). In conclusion, the effect of dietary flavonoid intake on colorectal cancer risk differs according to flavonoid subclasses and CYP1A1 genetic variants.